Acoustic emission source localization using coupled piezoelectric film strain sensors. (November 2014) - Zhou, Changjiang; Zhang, Yunfeng
This article presents a method for localizing near-field acoustic emission sources in isotropic and homogeneous thick plate using coupled piezoelectric film strain sensors. This acoustic emission source localization method is based on the phase difference of the acoustic emission signals measured by two acoustic emission sensors spaced at a predetermined distance. This phase difference cancels out certain frequency contents of the measured acoustic emission signals, which can be related to the acoustic emission source direction. A theoretical formulation which predicts these trough frequency values and acoustic emission source direction angles for the coupled acoustic emission sensors is first presented. Rayleigh wave is employed since its wave speed does not change in homogeneous half space, and its amplitude is greater than other elastic wave modes. Both elastodynamic solution and experimental data are used to validate the acoustic emission source localization technique. It is seen that the theoretical predictions, elastodynamic solution, and the experimental results are in good agreement with each other. Experimental data from acoustic emission monitoring of a stiffened steel plate specimen under fatigue loading are also used to test this method. Results show that the coupled piezoelectric film strain sensors are effective in determining the acoustic emission source direction in thick steel plates.